Cognitive impairment in systemic lupus erythematosus is negatively related to social role participation and quality of life: A systematic review. (September 2021) - Mendelsohn, Sierra; Khoja, Lina; Alfred, Sofia; He, Jennifer; Anderson, Melanie; DuBois, Denise; Touma, Zahi; Engel, Lisa
Introduction: At least 38% of patients with Systemic Lupus Erythematosus (SLE) experience cognitive impairment (CI). Patients report CI impacts their health-related quality of life (HRQoL) and social role participation. Objectives: To synthesize and critically appraise the quantitative literature on the relationship of CI to HRQoL and social role participation in individuals with SLE. Methods: Six electronic databases were searched in December 2018 and June 2020 by an information specialist. Two reviewers independently completed all screening phases and data extraction; a third reviewer resolved disagreements. The Mixed Methods Appraisal Tool was used to critically appraise the quality of included studies. Data has been synthesized and analyzed descriptively to present evidence on the relationship of CI to HRQoL and social role participation. Results: A total of 7182 references were identified and screened, with 14 articles included. Four of the included articles investigated the relationship between CI and HRQoL and all identified a negative relationship. Ten of the 14 studies investigated CI and social role participation, eight identified a negative relationship. There was heterogeneity of measures used between studies to examine CI, HRQoL, and social role participation. As such, results were interpreted descriptively and could not be pooled for meta-analysis. Conclusion: The presence of CI is negatively related to HRQoL and social role participation in patients with SLE. Healthcare professionals should be aware of this relationship so that it can be addressed in clinical practice. Further research, using consistent methods of quantifying CI, HRQoL and social role participation, is needed to enable data pooling.